The Effect Of Non-Physical Work Environment And Communication On Employee Performance At Pt Sari Sanwich Indonesia In South Tangerang - Banjal, Teul Panda; Ramadhan, Tubagus Guruh; Muslimat, Ade (Pasundan Social Science Development, 2025)
This study aims to determine the influence of non-physical work environment and communication on employee performance at PT Sari Sanwich Indonesia in South Tangerang. The method used is explanatory research with analysis techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study showed that the non-physical work environment had a significant effect on employee performance by 47.9%, the hypothesis test obtained t count > t table or (6.984 > 2.006). Communication had a significant effect on employee performance by 35.5%, the hypothesis test obtained t count > t table or (5.405 > 2.006). The non-physical work environment and communication simultaneously had a significant effect on employee performance with the regression equation Y = 8.757 + 0.429X1 + 0.379X2. The contribution of influence was 62.8%, the hypothesis test obtained F count > F table or (43.900 > 3.180).